Influence of telework during the Covid-19 pandemic on cervical pain (Research, Society and Development, 2023)
Objective. This is an integrative review to analyze the factors that influenced the prevalence of neck pain in the period before the Covid-19 pandemic and compare it with the factors that caused neck pain during the pandemic. Methods. The bibliographic survey was divided into two different steps: the first was to include articles published between 2015 and 2019 with the selection of 18 articles and used the following keywords: neck pain, work, and prevalence; the databases were PubMed and Google Academic. The second step was to analyze articles published between 2020 and 2021 in the context of the pandemic and the keywords were: cervical pain, telework, quarantine, and Covid-19. The searches were conducted using the Scielo, PubMed, and Google Scholar databases. Results. With the analysis of the results found, it became evident that mental health and incorrect ergonomics differentiated the occurrence of neck pain in the pandemic compared to the period before the pandemic. Conclusion. Furthermore, teleworking has a great tendency to be a working model in force even after the release of the pandemic. It is noticed that it will be necessary for companies to provide adequate means for employees to work remotely to decrease damage to physical health.